OPTIMALISASI KANDUNGAN KAPUR PADA MATERIAL ORGANIK UNTUK MENINGKATKAN KUAT GESER TANAH - Lestari, Nor Puji; Widoanindyawati, Vemi; Kusumastuti, Dianita Ratna; Triwardaya, Triwardaya; Marsudi, Marsudi (Bangun Rekaprima, 2024)
The main problems with soft soils are high moisture content, low soil mineral content, and high compressibility. The use of bacteria from organic materials to form lime compounds as adhesives in soft clay stabilisation has not been done. So this research is intended to improve the soil by stabilising soft clay soil with bacteria in organic materials.The method used in this research is experimental method. Variations of soybean powder mixture (organic material) used were 5 g/L, 10 g/L, 20 g/L, 30 g/L, and 40 g/L with reagent concentration of 1 mol/L. Furthermore, CBR (California Bearing Ratio) test specimens and Unconfine compressive test (UCS) specimens were made to determine the effect of the addition of lime compounds on soil strength. The concentration of 30 g/L produces optimum lime deposits. This is in line with the results of SEM and XRD tests. The UCS test showed that the soil cemented with lime produced the optimum shear strength at 14 days of curing, with a free press of 86.39 kPa. While for a period of more than 14 days the increase in the value of free compressive strength is relatively very small.